Pengaruh pertumbuhan ekonomi inklusif dan eksklusif terhadap tingkat kesejahteraan masyarakat provinsi di indonesia: analisis data Proksi - Rahmadi, Selamet; Hastuti, Dwi (Jurnal Paradigma Ekonomika, 2026)
This study aims to analyze the effect of the Gini Ratio, used as a proxy for exclusive and inclusive economic growth, on the Human Development Index (HDI), used as a proxy for the level of public welfare, across 34 provinces in Indonesia during the 2016–2024 period. The data were obtained from Statistics Indonesia and analyzed using simple panel data regression. Model selection was conducted using the Chow test and the Hausman test, both of which indicated that the Fixed Effects Model was the most appropriate estimation model. The results reveal that the Gini Ratio has a negative and statistically significant effect on HDI. This finding indicates that increasing income inequality tends to be associated with a decline in the quality of human development, whereas a more equitable income distribution may contribute to improved public welfare. The coefficient of determination of 85.11 percent indicates that most of the variation in HDI can be explained by the Gini Ratio within the research model. Therefore, provincial governments should strengthen policies aimed at promoting income equality, reducing poverty, and expanding equitable and sustainable access to education, healthcare, employment opportunities, and public services.